Association of Genetic Polymorphisms on VEGFA and VEGFR2 With Risk of Coronary Heart Disease. Issue 19 (May 2016) - Liu, Dongxing; Song, Jiantao; Ji, Xianfei; Liu, Zunqi; Cong, Mulin; Hu, Bo
Abstract : Abstract: Coronary heart disease (CHD) is a cardiovascular disease which is contributed by abnormal neovascularization. VEGFA ( vascular endothelial growth factor A ) and VEGFR2 ( vascular endothelial growth factor receptor 2 ) have been revealed to be involved in the pathological angiogenesis. This study was intended to confirm whether single nucleotide polymorphisms (SNPs) of VEGFA and VEGFR2 were associated with CHD in a Chinese population, considering pathological features and living habits of CHD patients. Peripheral blood samples were collected from 810 CHD patients and 805 healthy individuals. Six tag SNPs within VEGFA and VEGFR2 were obtained from HapMap Database. Genotyping of SNPs was performed using SNapShot method (Applied Biosystems, Foster, CA). Odd ratios (ORs) and their 95% confidence intervals (95% CIs) were calculated to evaluate the association between SNPs and CHD risk. Under the allelic model, 6 SNPs of VEGFA and VEGFR2 were remarkably associated with the susceptibility to CHD. Genotype CT of rs3025039, TT of rs2305948, and AA of rs1873077 were associated with a reduced risk of CHD when smoking, alcohol intake and diabetes were considered, while homozygote GG of rs1570360 might elevate the susceptibility to CHD (all P  < 0.05) for patients who were addicted to smoking or those with hypertension. All of the combined effects of rs699947 (CC/CA) and rs2305948 (TT), rs3025039 (TT) and rs2305948 (TT), rs3025039 (CT) and rs1870377 (AA) had positive effects on the risk of CHD, respectively (all P  < 0.05). By contrast, the synthetic effects of rs69947 (CA/AA) and rs1870377 (TA), rs699947 (CA) and rs7667298 (GG), rs699947 (AA) and rs7667298 (GG), rs1570360 (GG) and rs2305948 (TT), as well as rs1570360 (GG) and rs1870377 (AA) all exhibited adverse effects on the risk of CHD, respectively (all P  < 0.05). Six polymorphisms in VEGFA and VEGFR2 may have substantial influence on the susceptibility to CHD in a Han Chinese population. Prospective cohort studies should be further designed to confirm the above conclusions.